2014
DOI: 10.1002/jcb.24958
|View full text |Cite
|
Sign up to set email alerts
|

PPARG Modulated Lipid Accumulation in Dairy GMEC via Regulation of ADRP Gene

Abstract: Peroxisome proliferator-activated receptor-gamma (PPARG) is considered to be a central regulator of lipid metabolism in mammary cells. Adipose differentiation-related protein (ADRP), a member of PAT family (Perilipin, ADRP, TIP47 family), plays a key role in lipid accumulation in mammary gland. It has been found that PPARG significantly promoted lipid storage in goat mammary epithelial cells (GMEC), which was abolished after knockdown of ADRP gene. The results of real-time PCR, Western blot and luciferase repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 43 publications
9
54
0
Order By: Relevance
“…In the present study, the marked upregulation of PLIN2 in PPARG-overexpressing GMEC is consistent with recent data indicating that PPARG could directly bind to the promoter of PLIN2 and modulate the lipid formation in GMEC [13]. Less is known about the role of CIDEA in lipid droplet formation in ruminant mammary cells; however, it was the only CIDE isoform which was upregulated significantly after overexpression of PPARG plus ROSI.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the marked upregulation of PLIN2 in PPARG-overexpressing GMEC is consistent with recent data indicating that PPARG could directly bind to the promoter of PLIN2 and modulate the lipid formation in GMEC [13]. Less is known about the role of CIDEA in lipid droplet formation in ruminant mammary cells; however, it was the only CIDE isoform which was upregulated significantly after overexpression of PPARG plus ROSI.…”
Section: Discussionsupporting
confidence: 92%
“…It was also demonstrated that PPARG stimulates the synthesis of monounsaturated fatty acids in dairy goat mammary epithelial cells (GMEC) via the control of stearoyl-coenzyme A desaturase ( SCD ) [2]. Furthermore, our recent data revealed that PPARG could modulate lipid accumulation via regulation of Perilipin 2 ( PLIN2 ) gene expression in GMEC [13]. Although some work [2, 3] has been performed to study the function of PPARG in ruminant mammary cells, a comprehensive dataset on gene profiles altered by PPARG is not available.…”
Section: Introductionmentioning
confidence: 99%
“…PPARγ has a central role in regulating the transcriptional levels of several genes involved in lipid metabolism in the mammary gland, including SREBP1 (Bionaz and Loor, 2008;Shi et al, 2013), which in turn regulates de novo FA synthesis through ACCα and FAS (Liang et al, 2002;Rudolph et al, 2010). Furthermore, it has been shown that the activation of PPARγ signaling in goat mammary epithelial cells promotes the accumulation of lipids by up-regulating ADPH expression and promoter activity (Kang et al, 2015). Perinatal exposure to BPA could have directly or indirectly activated PPARγ signaling in the mammary gland, thereby increasing both de novo FA synthesis and ADPH mRNA expression in the BPA52 F1 lactating rats on LD10.…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ is known to regulate both the expression of several genes involved in de novo FA synthesis, such as SREBP1, and lipid droplet storage in mammary glands during lactation (Kang et al, 2015;Shi et al, 2013). Therefore, to examine whether BPA-induced changes in the milk lipid fraction are associated with alterations in lipid metabolism regulation, the mRNA expression levels of PPARγ and SREBP1 were evaluated in F1 BPA perinatally exposed dams at mid-lactation.…”
Section: Pparγ and Srebp1 Mrna Expression Was Modified By Perinatal Ementioning
confidence: 99%
“…Triacylglycerol concentration was normalized to total protein determined by BCA Protein assay kit (Pierce/Thermo, USA) as described previously. 4 , 55 …”
Section: Triacylglycerol Assaymentioning
confidence: 99%